Silicon priming enhances growth and photosynthetic pigments in rice plants under drought stress - Nina Fadia Hayya; Diah Rachmawati (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2025)
Rice (Oryza sativa L.) variety 'Inpari 24 Gabusan' offers high nutritional value and a short growth cycle that is ideal for further development. This study aimed to assess the effect of silicon priming on the growth and photosynthetic pigments of rice 'Inpari 24 Gabusan' during the vegetative stage under drought conditions. A completely randomized design (CRD) was used with two factors: sodium metasilicate (Na₂SiO₃) concentrations (0 mM, 20 mM, 40 mM, and 60 mM) and field water capacity (100, 75, and 50%). Germination parameters (percentage and rate of germination, and seed vigor index) and vegetative parameters (plant height, leaf number, root length, biomass) were measured. Leaf chlorophyll and carotenoid content were also assessed. Results showed that silicon priming increased the germination rate from 57.17% at 0 mM to 63.83% at 60 mM. Seed vigor index significantly improved at 60 mM. However, sodium metasilicate concentration had no significant effect on the percentage of germination. Priming at 40 mM and 60 mM significantly enhanced growth and chlorophyll content, particularly at 100% and 75% field capacity. Under 50% field capacity, growth improvements were more limited due to water deficit. Higher sodium metasilicate concentrations also enhanced chlorophyll content, improved photosynthetic efficiency and drought tolerance. Keywords: carotenoid; chlorophyll; field capacity; germination; sodium metasilicate